Advanced Tools for ITER Tritium Plant System Modeling and Design. (3rd July 2020) - Nougués, J. M.; Feliu, J. A.; Campanyà, G.; Iraola, E.; Batet, L.; Sedano, L.
Abstract: Chemical plant system modeling experience based on the use of largely validated commercial modeling tools such as the Aspen HYSYS is adapted and exploited to develop numeric routines for unitary isotopic operations, including permeation, cold trapping, reversible absorption, and cryogenic distillation, for the ITER tritium plant systems. Model prediction capabilities and isotopic database inputs for first-principle models are discussed. Numeric implementation of the Aspen HYSYS routines are presented.